Synthetic lethality of RB1 and aurora A is driven by stathmin-mediated disruption of microtubule dynamics - Junfang Lyu (Nature Portfolio, 2020)
Retinoblastoma susceptibility gene (RB1) is frequently mutated in lung cancers. Here the authors perform chemical and genetic vulnerability screens and identify aurora A kinase (AURKA) as a synthetic lethal candidate for RB1-deficient lung cancer cells and that AURKA inhibition sensitizes these cells to mitotic cell death.